2005
DOI: 10.1523/jneurosci.0506-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

cAMP Responsive Element-Binding Protein Phosphorylation Is Necessary for Perirhinal Long-Term Potentiation and Recognition Memory

Abstract: We established the importance of phosphorylation of cAMP responsive element-binding protein (CREB) to both the familiarity discrimination component of long-term recognition memory and plasticity within the perirhinal cortex of the temporal lobe. Adenoviral transduction of perirhinal cortex (and adjacent visual association cortex) with a dominant-negative inhibitor of CREB impaired the preferential exploration of novel over familiar objects at a long (24 h) but not a short (15 min) delay, disrupted the normal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
105
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 60 publications
(92 reference statements)
4
105
1
Order By: Relevance
“…LTP in the perirhinal cortex is associated with an increase in BDNF secretion in the first 5-12 post-stimulation and this LTP can be blocked by inhibiting the BDNF receptor TrkB (Aicardi et al, 2004). Perirhinal LTP can be blocked by inhibiting CREB as shown by adenoviral transduction of a CREB-inhibitor onto perirhinal slices (Warburton et al, 2005) but it appears to be independent of L-type voltage-dependent Ca 2+ channel activation (Seoane et al, 2009). The induction of LTP in the perirhinal cortex has also been demonstrated to be GABA A -dependent as enhancement of GABA A receptor function by lorazepam disrupts the induction of LTP in neurons within layers II/III (Wan et al, 2004).…”
Section: Synaptic Plasticity In the Perirhinal Cortexmentioning
confidence: 99%
See 4 more Smart Citations
“…LTP in the perirhinal cortex is associated with an increase in BDNF secretion in the first 5-12 post-stimulation and this LTP can be blocked by inhibiting the BDNF receptor TrkB (Aicardi et al, 2004). Perirhinal LTP can be blocked by inhibiting CREB as shown by adenoviral transduction of a CREB-inhibitor onto perirhinal slices (Warburton et al, 2005) but it appears to be independent of L-type voltage-dependent Ca 2+ channel activation (Seoane et al, 2009). The induction of LTP in the perirhinal cortex has also been demonstrated to be GABA A -dependent as enhancement of GABA A receptor function by lorazepam disrupts the induction of LTP in neurons within layers II/III (Wan et al, 2004).…”
Section: Synaptic Plasticity In the Perirhinal Cortexmentioning
confidence: 99%
“…Immediate early gene imaging studies have shown that the perirhinal cortex is activated following object recognition tasks (Wan et al, 1999;Aggleton and Brown, 2005;Warburton et al, 2005) and following the presentation of novel visual stimuli (Zhu et al, 1995b(Zhu et al, , 1996(Zhu et al, , 1997, thus indicating that the perirhinal cortex plays a central role in novelty detection. Lesions of the perirhinal cortex have been shown to impair performance in the object recognition task (Ennaceur et al, 1996;) and more recent work has shown that the perirhinal cortex is required for the encoding, consolidation and retrieval of object recognition memory (Winters and Bussey, 2005a,b;Winters et al, 2008).…”
Section: Object Recognition Memorymentioning
confidence: 99%
See 3 more Smart Citations